Genome Sequence Resource for Xanthomonas oryzae pv. oryzae (Causal Agent of Bacterial Leaf Blight of Rice) Isolated from Pakistan - Khansa Ejaz; Muhammad Zakria; Jose Huguet Tapia; Peiqi Zhang; Ali Faiq; Rafia Ahsan; M. Arif; M. Asif; Frank F. White; Sumera Yasmin (PhytoFrontiers, 2023)
Bacterial leaf blight, one of the most destructive diseases of rice, is prevalent in the major rice-growing regions of the world. Bacterial leaf blight is caused by Xanthomonas oryzae pv. oryzae (Xoo) and greatly affects the quantity and quality of the rice crop. We sequenced the whole genome of Xoo isolated from a Basmati rice-growing region of Pakistan using long-read Oxford Nanopore sequencing technology. About 637 MB of data was retrieved, corresponding to 133× genome sequencing coverage. The final assembly yields a circular chromosome of 4,930,682 bp. The complete genome of the Xoo isolate from Pakistan will enhance sequence resources for global comparison of Xoo diversity across the region. [Figure: see text] Copyright © 2023 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.